FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU DALAM PEMBERIAN MP-ASI DINI DI PUSKESMAS SIRAPIT KABUPATEN LANGKAT TAHUN 2020 - Sevty Lolo Marheyeni (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2020)
THE RELATED FACTORS WITH MOTHER'S BEHAVIOR IN PROVIDING EARLY COMPLEMENTARY FEEDING AT COMMUNITY HEALTH CENTRE OF SIRAPIT LANGKAT REGENCY IN 2020 Sevty Lolo Marheyeni Manik1, Arlinda Sari Wahyuni 2,Bahtera Bindavid Purba 3 Email: sevtyburhan@gmail.com 1Masters Program Faculty Alumni of Public Health Institute of DELI HUSADA Deli Tua 2Lectureof Public Health Institute of DELI HUSADA Deli Tua ABSTRACT Appropriate complementary feeding is greatly influenced by the behavior of mothers who have babies. This study is to analyze what factors are related to maternal behavior in providing early complementary feeding in the Serapit Health Center in Langkat Regency in 2019. This research is an analytic study with a cross sectional approach to 86 mothers who have babies aged 6-12 months in the region the work of the Sirapit District Health Center in Langkat Regency. Sampling was done by purposive sampling with inclusion and exclusion criteria. The research instrument uses a structured questionnaire that has been tested for validity and reliability then is analyzed univariately and bivariately using the Chi Square test. Analysis of factors related to maternal behavior in giving early complementary feeding is used logistic regression at 95% confidence level (α = 0 , 05). The results of this study indicate that the majority of respondents who have poor knowledge 73.3%, who have low education 76.7%, mothers who are 75.6%, poor attitude 74.4%, socio-cultural that is not entrenched 76.7 % and poor maternal behavior 54.7%. The results of bivariate analysis revealed that knowledge (p = 0.003), education (p = 0.005), occupation (p = 0.012), attitude (p = 0.006) and social culture (p = 0.001) were significantly related to maternal behavior in giving Early breastfeeding in the Sirapit Community Health Center. It is therefore recommended for health workers to further improve health education to mothers, families and the community to increase understanding of the importance of providing correct and appropriate early complementary feeding. Keywords: Knowledge, Education, Work, Attitude, Socio-Culture, Maternal Behavior, Early Complementary Feeding